Rancang Bangun Mesin Pengaduk Bahan Karet dengan Pendekatan Antropometri untuk Meningkatkan Efisiensi Waktu Kerja (Studi Kasus: CV. Nur Hidayah) - Aloysius Alviano Arya Lelana; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to design and build a rubber material mixing machine using an anthropometric approach to improve work time efficiency at CV. Nur Hidayah. The main problem faced is that the rubber material mixing process is still done manually, so it takes a long time, a large workforce, and has the potential to cause fatigue and the risk of work injuries. The method used in this study is an engineering design method with an anthropometric approach, namely adjusting the dimensions of the machine to the worker's body size to create comfort and work efficiency. The data required are worker data, worker anthropometric data, and cost data. The results obtained for the body measurements used include a standing elbow height of 101 cm, a forward arm reach length of 70 cm, a knee height of 51 cm, and a hand span length of 149 cm. Before the machine was installed, CV. Nur Hidayah still manually mixed rubber tacks with a process time of approximately 58 minutes. After the mixing machine was designed and implemented, the mixing time was successfully shortened to approximately 15 minutes.